2020
DOI: 10.1177/0972262920959523
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review on Diversity and Inclusion at Workplace, 2010–2017

Abstract: Purpose: The article highlights various studies conducted in the field of diversity and inclusion at workplace. This helps us to understand the evolution of diversity and inclusion and identify future research gaps. Methodology: The article employs a citation analysis technique to analyse the citation index of journals and authors based on the data collected from various databases such as Social Sciences Citation Index, Emerging Sources Citation Index, and SCImago (2010–2017). For the analysis, journals releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…However, this study suggests an additional sense of “ethical diversity.” VAD views were linked to diversity in the sense of an organizational strength where there is inclusion and safety for staff of different genders, cultures, and sexualities (Garg and Sangwan 2021 ). While some previous writing has linked ethical diversity with religious or cultural diversity specifically (Irvine, Mcphee, and Kerridge 2002 ; Schmidtke and Cornel 2020 ; Harrison 2012 ), framing a spectrum of ethical views on VAD within a health service as a type of organizational diversity and inclusion is a new finding.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study suggests an additional sense of “ethical diversity.” VAD views were linked to diversity in the sense of an organizational strength where there is inclusion and safety for staff of different genders, cultures, and sexualities (Garg and Sangwan 2021 ). While some previous writing has linked ethical diversity with religious or cultural diversity specifically (Irvine, Mcphee, and Kerridge 2002 ; Schmidtke and Cornel 2020 ; Harrison 2012 ), framing a spectrum of ethical views on VAD within a health service as a type of organizational diversity and inclusion is a new finding.…”
Section: Discussionmentioning
confidence: 99%
“…The 21st century has witnessed a heightened emphasis on diversity and inclusion within the corporate sphere. This shift can be attributed to several factors, including the increased participation of women in the workforce (Garg & Sangwan, 2021), the involvement of individuals from diverse backgrounds and multiple generations, and the renewed sociopolitical push for the inclusion of immigrants (Ortlieb & Sieben, 2014). The rising diversity has raised several inquiries, especially regarding its impact on firm productivity and the emotional well-being of individual workers (Hauret & Williams, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has been predicted that in 2022 and beyond HR executives around the globe will strive for a fairer working environment (Gartner, 2021). This has resulted due to unprecedented and increasing participation of all the individuals with various geographical backgrounds, and nationalities at workplaces (Garg & Sangwan, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Interpersonal intensification of the workplace driven by the increased emphasis on collaboration, teamwork, projects and complex social networks (Gibson et al, 2003), combined with productivity pressures, increasing diversity (situational, informational, expertise, perspective, social category, attitudinal, disability, personality etc.) (Wong & Birnbaum-More, 1994), and greater demands for inclusion (Garg & Sangwan, 2021), has increased the potential for greater process losses, frustration, and conflict (Mohammed & Angell, 2004;Puck et al, 2011;Thatcher et al, 2003;Thatcher et al, 1998). Research on the translation of diversity, teamwork and projects into organizational value under escalating performance pressures (Pavez et al, 2021), has identified the importance of moderating variables that promote efficient and productive forms of openness, supportiveness, and conflict management (Jehn et al, 1999;Liu et al, 2020;Pelled et al, 1999;Puck et al, 2011).…”
Section: Management Orientation In Project Teamsmentioning
confidence: 99%